PENGARUH VOLUME KENDARAAN TERHADAP TINGKAT KERUSAKAN JALAN PADA JALAN PRABU RANGKASARI KOTA MATARAM - NI LUH PUTU AYU VERRA WIDAYANTI; LALU HARDI WIJAYA; AMINULLAH AMINULLAH; TJOK ISTRI WIDYANI UTAMI DEWI SUDIRA (SOSIAL SAINS DAN TEKNOLOGI, 2022)
This research is entitled "The Effect of Vehicle Volume on the Level of Road Damage on Jalan Prabu Rangkasari, Mataram City". The aim is to determine the effect and volume of vehicles with damage levels on flexible pavements. This type of research uses a descriptive and qualitative type of approach which is the type of research that is actually appropriateThe results showed that the value of road damage (Nr) on Jalan Prabu Rangkasari in the north - south and south - north directions was 68.2. Traffic volume at peak hours is based on passenger car units (pcu)/hour on Jalan Prabu Rangkasari in the direction of North – South 663 smp/hour and South – North of 536 smp/hour. The results of the equation from the traffic volume analysis, the value of road damage and time are y = 0.00473x1+0.00154x2+15.245, with non-linear regression (R2) or the correlation between variables x and y = 0.937. The results of this equation are useful for knowing the prediction of the value of road damage or Nr that will occur at the next time on the Prabu Rangkasari road, Mataram City,West Nusa Tenggara Province